Síntesis y validación de metodologías y algoritmos para la determinación de parámetros de calidad de energía eléctrica - Ganazhapa Jiménez, Byron Oswaldo (2014)
In this project is performed the design and validation of an analyzer of power quality of a three-phase, with the capacity of data transmission through Ethernet connection for recording and display of electrical parameters. For its development, it aims to fulfill four basics steps: first, to define the methodology for determining an electric parameter from the analytic point of view. As a second step, it is proposed to synthesize the methodology proposed in source code based on a programming language that supports Open Source development platforms. As a third step, is proposed to design the blocks of conditioning and digitizing the voltage and current signals acquired. And fourth step, it is proposed to perform a validation of the complete system (hardware, firmware and software) with a reference instrument.